1988
DOI: 10.1159/000226627
|View full text |Cite
|
Sign up to set email alerts
|

Lectin Binding in Human Breast Cancer: Clinical and Pathologic Correlations with Fluorescein-Conjugated Peanut, Wheat Germ and Concanavalin A Binding

Abstract: Cell surface glycoconjugates of human breast cancer tissue were investigated using FITC peanut (PNA), wheat germ (WGA) and jackbean (concanavalin A; Con A) agglutinins. Although PNA and WGA binding patterns differed when normal and malignant breast tissues were compared, the specificity of this finding was poor and neither PNA nor WGA binding correlated with oestrogen receptor status or clinical outcome. Con A binding on the other hand was not seen in normal breast tissue. The percentage of Con-A-positive (Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…The resultant CIN ratios for PNA showed no correlation with the ER/PR content of the breast-tumor tissues. This is in contrast to the studies of Bocker et al (1984) and Dansey et al (1988), in which T-antigen expression was reported to posi-tively correlate with the expression of ER in breast cancer. These discrepancies may be due to differences in reagents or methods of analysis used in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The resultant CIN ratios for PNA showed no correlation with the ER/PR content of the breast-tumor tissues. This is in contrast to the studies of Bocker et al (1984) and Dansey et al (1988), in which T-antigen expression was reported to posi-tively correlate with the expression of ER in breast cancer. These discrepancies may be due to differences in reagents or methods of analysis used in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Various lectins with specific carbohydrate binding properties have been used to identify specific cell surface carbohydrate compositions in normal or neoplastic cells (Dansey et al, 1988;Langkilde et al, 1989bLangkilde et al, , 1989cAoki et al, 1990;Hohenberger et al, 1990;Kakeji et al, 1994;Schumacher et al, 1994;Takahashi et al, 1994;Mody et al, 1995). WGA has been shown to react with cell membrane glycoproteins in a wide variety of neoplastic tissues (Willmott and Simpson, 1983;Walker, 1984;Kellokumpu et al, 1986;Dansey et al, 1988;Langkilde et al, 1989a;Bresalier et al, 1990;Welch et al, 1990;Mody et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…WGA has been shown to react with cell membrane glycoproteins in a wide variety of neoplastic tissues (Willmott and Simpson, 1983;Walker, 1984;Kellokumpu et al, 1986;Dansey et al, 1988;Langkilde et al, 1989a;Bresalier et al, 1990;Welch et al, 1990;Mody et al, 1995). When WGA was used to generate lectin-resistant clones of cultured cancer cells, most resulting clones showed a remarkable loss of metastatic capabilities (Stanley et al, 1980;Kerbel et al, 1982;Ishikawa et al, 1988;Ishikawa and Kerbel, 1989;Kim et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A similar selection can be operative with respect to naturally occurring immunoglobulin fractions, among them one with selectivity to 9-0-acetylated sialic acid (Neu5,9-Ac 2 ) [28,29]. Due to the suggested relevance of concanavalin A (Con A) reactivity for metastasis formation and survival from a cell model and histochemical analysis [26,30,31], this plant lectin was also part of the glycohistochemical panel of this study. Binding of this lectin was compared with that of the collectin to infer differences of the two lectins with identical monosaccharide specificity.…”
Section: Introductionmentioning
confidence: 99%